(untitled) (The Journal of Medicine, Humanity and Media, 2024)
Robot assisted surgery, as one of the ways in which artificial intelligence is applied in the medical and health field, has attracted much attention. The discussion of scientific topics by users is different from the perspective of experts and has its own uniqueness, while also being influenced by media agendas. In the context of media platformization, this study takes the videos relating to robot assisted surgery in the Douyin platform as an example and uses the bi-term topic model (BTM) to explore the focus of media and corresponding user reviews on this scientific topic. Research has found that there are more diverse media outlets for agenda setting in robot assisted surgery, with medical professionals as the main communicator. The agenda attributes set by different sub media outlets have distinct characteristics, including international competition, technological innovation, safety, price, and universal benefit. Although these attributes are reflected in the user agenda (price, inclusiveness, monopoly, doctors, network, human-machine, and out of control), the discussion of attributes by users reflects many more detailed risk aspects, providing reference for ethical governance of specific applications of artificial intelligence in healthcare.